Pelatihan Bahasa Arab: Mufrodat At-Ta'aruf dengan Metode Pembelajaran Interaktif pada Anak-Anak di Majelis Darul Anwar Kampung Sukajaga Cihanjawar Purwakarta - Raisa Nisrina; Rohendi Rohendi; Taufik Luthfi; Riyan Haqi Khoerul Anwar (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
The Arabic language training on mufrodat at-ta'aruf was conducted at Majelis Darul Anwar, Kampung Sukajaga, Cihanjawar, Purwakarta to introduce basic vocabulary related to name, age, and home address to children. This training applied an interactive learning method, incorporating educational games, conversation exercises, and singing to create an engaging and effective learning environment. Prior to implementation, surveys, observations, permissions, and socialization with the community were conducted to ensure support and active participation from both children and their parents. The results indicate that interactive methods significantly enhance children's understanding and interest in learning Arabic. Children found it easier to memorize vocabulary through activities involving direct interaction and repeated practice. Additionally, community support, particularly from the majelis owner and parents, played a crucial role in the training's success. However, it was observed that differences in children's educational backgrounds influenced their comprehension levels, highlighting the need for continuous training. This training serves as a foundation for children to familiarize themselves with Arabic from an early age. For future improvements, it is recommended to utilize more diverse learning media, conduct training regularly, and collaborate with local educational institutions.